STRATEGI FUNDRAISING DAN FILANTROPI DALAM PENGELOLAAN LEMBAGA AMIL ZAKAT INFAQ DAN SHADAQAH MUHAMMADIYAH (LAZISMU) DI KABUPATEN SAMBAS - Guntur; Sri Sunantri; A.Rafik (Jurnal Ilmiah Al-Muttaqin, 2021)
Strategy is a method used to carry out an activity to achieve a goal. Through the strategy can determine a plan that will be produced. LAZISMU Sambas Regency is an institution that operates as a manager of infaq and shadaqah zakat funds, of course, has a mature strategy. This is very influential on the programs being run and plays an important role in collecting funds from donors and distributing them to mustahik. The purpose of this research in general is to find out how to raise funds in the management of the amil zakat infaq and shadaqah Muhammadiyah institutions in Sambas Regency, to find out how to channel funds in the management of the amil zakat infaq and shadaqah Muhammadiyah institutions in Sambas Regency, and to find out the opportunities and challenges. faced in the management of the amil zakat infaq and shadaqah Muhammadiyah institutions in Sambas Regency.